Putting Brands in Their Place: How a Lack of Control Keeps Brands Contained. (June 2013) - Cutright, Keisha M.; Bettman, James R.; Fitzsimons, Gavan J.
New brand extensions can push a brand outside its typical boundaries. In this article, the authors argue that people's acceptance of such extensions depends on their feelings of control. Across several studies, the authors demonstrate that when feelings of personal control are low, consumers and managers seek greater structure in brands and thus reject brand extensions that do not seem to fit well with the parent brand. The authors also identify important boundary conditions that illustrate when consumers are most likely to punish a brand for poor-fitting brand extensions and how the effect can be mitigated.